Posturography table is a good test to evaluate the anterior cruciate Ligament reconstruction?. Issue 5 (31st May 2019) - Wein, Frank; Peultier, Laetitia; Mainard, Didier; Perrin, Philippe
Introduction: The success of anterior cruciate ligament reconstruction (ACLR) is assessed using subjective and functional scores, as well as measurements of knee laxity. The latter is often quantified using instrumented laximetry devices, which measure 'static' anterior tibial translation, though recent studies suggested more comprehensive "dynamic" analyses such as jump tests. To facilitate and improve dynamic stability analyses, a proprioception table was adapted to evaluate knees before and after ACLR, though the accuracy and pertinence of its measurement have not yet been demonstrated. Objectives: To determine whether proprioceptive analysis following ACLR provides meaningful and helpful information to guide surgeons and physiotherapists with postoperative rehabilitation and return to sports. Methods: We conducted a prospective study, on a population of 50 amateur or professional sports patients, who received ACLR by the one surgeon (FW). Preoperative and 6-months assessments included GnRB laxity analysis and proprioceptive dynamic stability analysis, with evaluation of the bearing area under 6 different conditions: open eyes (C1), closed eyes (C2), vision distorted by virtual reality headset (C3), open eyes on unstable support (C4), closed eyes on unstable support (C5) and distorted vison on unstable support (C6); a calculation of the C4/C1 ratio enabled appreciation of visual compensations in the proprioceptive capacity, and dependence on visual inference (low ratios indicate greater recourse to visual afference). A complementary analysis of muscular strength by isokinetic assessment was also performed at 6 months followup. Results: There was a significant improvement in proprioception table stability at 6 months compared to the preoperative condition at the C4 (470 vs 440 mm 2 ), C5 (1710 vs 1315 mm 2 ) and C6 (1330 vs 1210 mm 2 ) assessments. For 32 patients evaluated by GnRB, differential laxity at 6 months was less than 5 mm at 200 N, and isokinetic muscle strength measurement was less than 20% different between the knee healthy and the operated knee, or between quadriceps and hamstrings. Proprioceptive quality was variable, with significant visual offsets in some cases (C4/C1 ratio, 0.5 to 16.2). Conclusion: Patients, who have good results in laximeter tests and isokinetic muscle strength measurement, may have a poor proporioception quality with significant visual offsets. The proprioception analysis at 6 months following ACLR could therefore be important to consider rehabilitation and sports recovery.